Teacher's Strategies in Developing Early Children's Reading Ability - Sulaiman, Nur Ashikin Binti; Pransiska, Rismareni (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
Reading is an important skill because children must learn to read from an early age. This research aims to evaluate teachers' strategies in developing the early reading skills of children aged 5-6 years at Kindergarten Ilmu Hayati, Kuala Lipis, Pahang, Malaysia. Qualitative methods are used with case study approach in observation and interviews. The results showed that weekly learning techniques were consistent, but variations in daily courses were applied. The role of parents is very important in children's reading development, and children who are guided by parents at home tend to develop reading skills more quickly. The habit of attending the second learning session is influenced by parents who work in the afternoon. The theory of children's reading development in Malaysia emphasizes the importance of readers' interactions with texts to build meaning. Effective reading strategies include the use of a variety of strategies according to the text and context to achieve specific goals.